2018
DOI: 10.17582/journal.aavs/2018/6.9.359.365
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Organic Acid as an Alternative to Antibiotics Drugs on Productive and Physiological Performance of Broilers Ross 308

Abstract: H igh levels of production and efficient feed conversion are the need of the modern poultry industry, which to a certain extent could be achieved by the use of specific feed additives. Antibiotic feed additives as growth promoters have long been supplemented to poultry feed to stabilize the intestine microbialflora, improve the general performances and prevent some specific intestinal pathology (Hassan et al., 2010). However, due to the emergence of microbes resistant to antibiotics which are used to treat hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some studies have demonstrated the efficiency of butyric acid as an antimicrobial additive against pathogens that cause major losses in poultry production, such as Eimeria spp. (Ali et al, 2014;Song et al, 2017), Salmonella (Van Immerseel etal., 2004Fernandez-Rubio et al, 2009;Menconi et al, 2013;Cerisuelo et al, 2014), and Clostridium (Timbermont et al, 2010;Mohamed et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated the efficiency of butyric acid as an antimicrobial additive against pathogens that cause major losses in poultry production, such as Eimeria spp. (Ali et al, 2014;Song et al, 2017), Salmonella (Van Immerseel etal., 2004Fernandez-Rubio et al, 2009;Menconi et al, 2013;Cerisuelo et al, 2014), and Clostridium (Timbermont et al, 2010;Mohamed et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The gizzard weight obtained, however, is lower than that reported by Malik et al (2016) in broiler chickens fed with 0.05% probiotic, 0.20% acidifier, and their combination, namely 2.37% to 2.56%. Ali et al (2018) also reported higher gizzard weight (2.06%) in broilers fed with organic acids as a substitute for antibiotics.…”
Section: Effect Of Treatment On Percentage Of Internal Organs Of Broimentioning
confidence: 85%